Association between temporal resolution and Specific Language Impairment: The role of nonsensory processing. Issue 10 (October 2015) - Alvarez, Waleska; Fuente, Adrian; Coloma, Carmen Julia; Quezada, Camilo
Abstract Introduction Many authors have suggested that a perceptual auditory disorder involving temporal processing is the primary cause of Specific Language Impairment (SLI). The aim of this study was to compare the performance of children with and without SLI on a temporal processing task controlling for the confounding of verbal short-term memory and working memory. Method Thirty participants with SLI aged 6 years were selected, along with 30 age- and gender-matched participants with typical language development. The Adaptive Test of Temporal Resolution (ATTR) was used to evaluate temporal resolution ability (an aspect of temporal processing), and the digit span subtest of the Wechsler Intelligence Scale for Children was used to evaluate auditory short-term memory and working memory. Results The analysis of covariance showed that children with SLI performed significantly worse than children with typical language development on the temporal resolution task (ATTR), even when controlling for short-term memory and working memory. Statistically significant correlations between ATTR and digit span were found for the group of children with SLI but not for the children with typical language development. Conclusion Children with SLI showed significantly worse temporal resolution ability than their peers with typical language development. Such differences cannot be attributed solely to the immediate memory deficit associated with SLI.